Structure Design and Analysis of End-effector for Traditional Chinese Medical Massage Manipulator - Zhang Mingliang; Shi Zhixin; Luo Yufeng; Ye Meiyan (Jixie chuandong)
Firstly，in terms of traditional Chinese medical massage techniques—pushing method， pressing method， kneading method and rolling method， the characteristics of each massage technique are analyzed， and the degrees of freedom（DOF） of the 4 kinds of massage technique mechanism are obtained. Then， according to the DOF required by the mechanism， the overall design scheme of the mechanism is proposed. As for the parallel mechanism， the topological structures are designed and the DOF is analyzed. At last the direct and inverse solutions of the parallel mechanism are discussed， and the 3D modeling and kinematics simulation are carried out. The results show that the parallel mechanism not only has a simple structure and easy solution of position analyses， but also satisfied the requirements of various massage techniques mentioned above， the theoretical support for the practical application of traditional Chinese medical massage manipulator is provided.